Hand, foot and mouth disease in children: a systematic review - Herrera Ortiz, José Uberli (2024)
Hand, foot and mouth disease is a recurring contagious infection in children living under poor sanitary conditions, especially in developing countries, where a substantial increase in the disease has been reported in recent years. The study aimed to describe and analyze the occurrence of such disease in children, focusing on the most outstanding theoretical aspects that characterize it. For this purpose, a systematic review of the literature was conducted in PubMed, Google Scholar and Latin American and Caribbean Literature in Health Sciences (LILACS) using logical operators such as "EMPB" OR "Coxsackie A16" AND "Children" AND "Coxsackievirus Infections" AND "Child". A total of 584 research studies in Spanish and English published between 2010 and 2022 were identified, from which, after a scientific quality assessment process using checklists, quality criteria and relevant strength of recommendation and the PRISMA method, 40 articles were selected, to which three gray literature records were added, and 43 records were selected for quantitative data analysis. Hand, foot and mouth disease has a higher incidence in the Asian continent (India, Singapore, Japan and China), where epidemic outbreaks occur every year, mainly affecting the child population. It is caused by several serotypes such as A5, A7, A10, B1, B2, B3 and B5; however, Coxsackievirus A16 (CA16) and Enterovirus 71 (EV-71) are the most frequent among children. The disease causes fever, papulovesicular rash on the hands, feet and genitalia, as well as ulcerative lesions in the mouth. Its incubation period is four to six days, and it is transmitted by direct contact with secretions, fecal material or contaminated objects; its diagnosis is clinical and based on the patient's epidemiological history. As there is no specific treatment, only general measures are taken to alleviate the symptoms and prevent dehydration. Currently, there are outbreaks and serotypes that cause various complications such as encephalitis, myocarditis, hepatitis, acute hemorrhagic conjunctivitis, enteric diseases and herpangina, among others. For this reason, strict epidemiological surveillance of cases and contacts is required, along with education and communication interventions that reduce the risks of spread and infection.